Univariate and simplex optimization for the flow-injection spectrophotometric determination of copper using nitroso-R salt as a complexing agent - Purachat B. (2014)
A simple colorimetric flow-injection system for the determination of Cu(II) based on a complexation reaction with nitroso-R salt is described. The chemical and FIA variables were established using the univariate and simplex methods. A small volume of Cu(II) was mixed with merged streams of nitroso-R salt and acetate buffer solutions. The absorbance of the complex was continuously monitored at 492 nm. The calibration curve over the concentration range 1.0 - 7.0 μg ml-1 was obtained. The relative standard deviation for determining 4.0 μg ml-1 Cu(II) was 0.47% (n = 11). The detection limit (3σ) was 0.68 μg ml-1 and the sample throughput was 150 h-1. The validity of the method has been satisfactorily examined for the determination of Cu(II) in wastewater and copper ore samples. The accuracy was found to be high, because the student t-values were calculated to be less than the theoretical values when the results were compared with those obtained by FAAS.